Aplikasi Location Based Services (LBS) untuk Pendataan Potensi Daerah dengan Pendekatan Customer Relationship Management (CRM) - Bayu Hananto; Ridwan Raafiudin; Tri Rahayu (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
The purpose of this research is to build an application prototype for potential area data collection by using Location Based Service (LBS). In the prototype building stage of this application, use the method of Customer Relationship Management (CRM). This CRM method is for the benefit of a particular problem. The results obtained from this study are averaged average reliability (Reliability) with a value of 3.62, and category Usability category (Usability) with an average of 3.51. The model of this application will help local governments, to note the potential of their area.